Optimising Management of Patients with Heart Failure with Preserved Ejection Fraction in Primary Care (OPTIMISEHFpEF): rationale and protocol for a multi- method study. Issue 4 (2019) - , Faye Forsyth; , Richard Hobbs; , Thomas Blakeman; , Jonathan Mant; , Muhammad Zakir Hossain; , Christi Deaton; , Clare J Taylor; , Carolyn A Chew-Graham; , Emma Snowden; , Aaron Long; Edwards, Duncan
No abstract available